Metathesis and unmetathesis in Amarasi - Edwards, Owen (Language Science Press, 2020)
This book provides a complete analysis of synchronic CV -> VC metathesis in Amarasi, a language of western Timor. Metathesis and unmetathesis realise a paradigm of parallel forms, pairs of which occur to complement each other throughout the language. Metathesis in Amarasi is superficially associated with a bewildering array of disparate phonological processes including: vowel deletion, consonant deletion, consonant insertion and multiple kinds of vowel assimilation, any of which can (and do) vary by lect in their realisation. By proposing that Amarasi has an obligatory CVCVC foot in which C-slots can be empty, all these phonological processes can be straightforwardly derived from a single rule of metathesis and two associated phonological rules.